Profile of Handgrip Strength, Anthropometry, Nutritional Status and Activities of Daily Living Among Geriatrics at Karitas Nursing Home, Bandung - Thawaneswaaran Rajendran; Novitri Novitri; Yuni Susanti Pratiwi (Althea Medical Journal, 2015)
Background: Reduced handgrip strength is an aging process that influences the activities of daily living among elderly people. Handgrip strength varies greatly with age, gender, anthropometric measurement and nutritional status. This study aimed to determine the profile of handgrip muscle strength, physical characteristic, nutritional assessment and activities of daily living among elderly Methods: This study was conducted at Karitas nursing home, Bandung on September 2012. This is a descriptive study by collecting primary data from 28 elderly people. Data were collected in 2 days within 2 weeks. The first data collection included details of anthropometric measurement and handgrip measurement. The second data collection included face to face interview using standardized questionnaire for mini nutritional assessment and Barthel index.Result: The mean age of the respondents was 74.14 ± 8.5189 years. The average reading on handgrip muscle strength was 30.84 ± 12.0175 lbs for right hand and 27.77 ± 11.3778 lbs for left hand. For anthropometric measurement, most of the respondents had normal weight body mass index status (39.3%). Nutritional status of respondents evaluated by mini nutritional assessment showed that most of the respondents were at risk of malnutrition (64.3%). The activities of daily living assessment based Barthel Index showed that half of the respondents were dependent in activities of daily living (50%).Conclusions: From this  study, it can be concluded that the grip strength of all the respondents are weaker. Majority have normal body weight, malnutrition risk, and half of the subjects are depend on others in doing their daily activities.Keywords: Activities of daily living, anthropometry, elderly, handgrip strength, nutritional status DOI: 10.15850/amj.v2n1.423